Study on the relationship between telomere length changes and recurrence of atrial fibrillation after radiofrequency catheter ablation. (29th May 2019) - Su, Changyang; Liu, Zheng; Gao, Yuanfeng; Liu, Ye; Hu, Rou‐Mu; Liu, Jia; Yang, Xiyan; Li, Shichao; Zhang, Yuan; Zuo, Kun; Cao, Boli; Luo, Jing; et al.
Abstract: Introduction: Advanced age is the foremost risk factor for atrial fibrillation (AF). Telomere length is a surrogate for biological aging, but the association between shortened leukocyte telomere length (LTL) and recurrence of AF (RAF) after ablation remains inconclusive. Methods: In this prospective analysis, 282 patients underwent an initial catheter ablation for paroxysmal or persistent AF. The association between RAF and LTL was analyzed by univariate and multivariate Cox regression, as well as time‐dependent receiver operating characteristic (ROC) analysis and Kaplan‐Meier analysis. Results: After a mean follow‐up of 14.20 ± 5.04 months, RAF was documented in 78 of the 277 patients who completed the study (28.16%). In Cox proportional hazards models, LTL, age, diagnosis to ablation time (DTAT), N‐terminal pronatriuretic peptide, and CHA2DS2‐VASc score were significantly associated with RAF. After multivariable adjustment, LTL and DTAT were predicted as independent risk factors for RAF with hazard ratio (HR) of 3.17 (95% confidence interval [CI]: 1.23‐8.15, P  = 0.017) and 1.43 (95% CI: 1.10‐1.86, P  = 0.007), respectively. In addition, ROC analysis indicated the potential diagnostic value of LTL with an area under the curve of 0.64 ( P  < 0.001; sensitivity = 60.3%, specificity = 57.8%), and an optimum cut‐off value of 1.040. LTL less than or equal to 1.040 was defined as shortened LTL, while LTL greater than 1.040 nonshortened LTL. Kaplan‐Meier analysis showed RAF rate curve was separated significantly between two groups (21.2% vs 35.9%, log‐rank test result P  = 0.007). Patients with shortened LTL might have a higher risk for RAF with HR = 1.84 ( P  = 0.008). Conclusions: Shortened LTL is an independent risk factor for AF recurrence. Shortened LTL could be a potential biomarker in predicting RAF after ablation.